Analisis Pengaruh Faktor Internal dan Faktor Eksternal terhadap Profitabilitas Bank Pembiayaan Rakyat Syariah di Indonesia - Elsa Oktaviani; Muhamad Umar Mai; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the magnitude of the influence of the variables FDR, NPF, Firm Size, Infalsi, and GDP on ROA at Rural Bank Syaria in Indonesia. The population used is Rural Bank Syaria registered with the OJK. The data used is secondary data derived from financial reports issued by OJK for the 2016-2020 period. The research method used is quantitative research with pane data regression analysis and is supported by Eviews 9 as a data processing application. The sample used in this study was 99 BPRS. From this study, the results obtained that simultaneously independent variables affect ROA. Partially the variabel FDR, firm size development and GDP have a positive and significant effect on ROA. The NPF variable partially has a negative and significant effect on ROA. And the inflation variable has no significant effect on ROA.